Comparative Analysis of the Formation of Energy Resource Prices in the Republic of Moldova, Romania and Ukraine - Timus, Angela; Sargu , Lilia (Acta Universitatis Danubius. Œconomica, 2024)
Energy infrastructure plays a crucial role in the economic growth and development of a country or region, it is an essential component of economic development, contributing to production efficiency, innovation, resource diversification, cost reduction and sustainability promotion. The growing attention to natural energy resources is closely related to their limited supply. Natural energy resources such as oil, natural gas and coal are exhaustible. These resources are being extracted from the earth at a faster rate than they can be replenished. One day, these resources will be completely depleted, which will have significant consequences for energy supplies. In this context, the authors decided to study the price formation of these energy resources for the neighboring countries of the Republic of Moldova, Romania and Ukraine. Dependence on imported natural energy resources can make a country or region vulnerable to supply disruptions, such as geopolitical conflicts, energy transport bottlenecks, or problems in import sources. This can affect a country's economic stability and energy security.